Makna Simbolik Tari Wayang Kaleng di Sanggar Etnika Daya Sora Kota Bogor - Haerul Tamimi; Een Herdiani; Lilis Sumiati (Universitas Sultan Ageng Tirtayasa, 2026)
The Wayang Kaleng dance is a form of creative dance that combines elements of tradition and contemporary creativity, thus containing various symbols that represent the cultural values of the community. This study aims to determine the symbolic meaning of the Wayang Kaleng dance at the Sanggar Etnika Daya Suara in Bogor City. This study uses a qualitative method with a descriptive analytical approach, which attempts to describe and interpret the symbolic meanings contained in the movements. The theoretical basis used in this study includes Ferdinand de Saussure's semiotic theory, which emphasizes the concept of signifier and signified. The results show that the Wayang Kaleng dance contains symbolic meaning manifested through the relationship between the signifier and signified in each movement.